The Effect of Using Online Matching Games on Englishclub.com in Enhancing Vocabulary Mastery at SMPN 19 Bekasi - Siti Nurhaliza; Chusnul Chotimah; Enci Zarkasih (English Lecturers and Teachers Association (ELTA), 2026)
The research investigates the effect of using online matching games on EnglishClub.com in enhancing vocabulary mastery among seventh-grade students at SMPN 19 Bekasi. A quasi-experimental approach with pretest-posttest control group structures was employed. The sample comprised 70 students divided into two groups: experimental (n=35) and control (n=35). Both pre-test and post-test vocabulary assessments were used. The data was analyzed using descriptive statistics, normality tests (Kolmogorov-Smirnov and Shapiro-Wilk), a homogeneity test (Levene's Test), and the Independent Samples T-Test in SPSS. The control class's mean post-test score (68.67) was somewhat higher than the experimental class's (57.33), and the control class's N-Gain Score (mean = 5.17) was slightly higher than the experimental class's (mean = 4.70). The Independent Samples T-Test for the N-Gain Score yielded Sig. (2-tailed) = 0.854, whereas Levene's Test yielded F = 0.461, Sig. = 0.500, demonstrating homogenous variance. The test result was not significant at α = 0.05, with a small effect size (Cohen's d = -.044). These data suggest that, for this population and treatment length, online matching games on EnglishClub.com did not generate a statistically or descriptively significant advantage over conventional education in vocabulary acquisition at the junior high school level. Keywords : Englishclub.com; matching games; online games; vocabulary mastery